2006
DOI: 10.1212/01.wnl.0000249114.52802.55
|View full text |Cite
|
Sign up to set email alerts
|

Prevention of menstrual attacks of migraine

Abstract: Although perimenstrual percutaneous estradiol showed benefit during treatment, this was offset by deferred estrogen withdrawal, triggering post-dosing migraine immediately after the gel was stopped. Further work could assess if this could be avoided by extending the duration of treatment with estradiol.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
96
0
6

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 147 publications
(102 citation statements)
references
References 22 publications
(31 reference statements)
0
96
0
6
Order By: Relevance
“…15 Estradiol 1.5 mg (gel patch applied to the upper thigh or arm) was associated with a 22% reduction in migraine days (estradiol ϭ 133 migraine days, placebo ϭ 171 migraine days; relative risk [RR] 0.78; CI 0.62-0.99, p ϭ 0.04). This improvement was temporary, as subjects reported a 40% increase in migraine days in the 5 days following treatment (RR 1.40; CI 1.03-1.92, p ϭ 0.03).…”
Section: Co-q10 (Water-soluble Disbursable Form Of Co-q10)mentioning
confidence: 99%
“…15 Estradiol 1.5 mg (gel patch applied to the upper thigh or arm) was associated with a 22% reduction in migraine days (estradiol ϭ 133 migraine days, placebo ϭ 171 migraine days; relative risk [RR] 0.78; CI 0.62-0.99, p ϭ 0.04). This improvement was temporary, as subjects reported a 40% increase in migraine days in the 5 days following treatment (RR 1.40; CI 1.03-1.92, p ϭ 0.03).…”
Section: Co-q10 (Water-soluble Disbursable Form Of Co-q10)mentioning
confidence: 99%
“…Oral estrogens (Calhoun 2004;Somerville 1975) and percutaneous estradiol showed benefit during perimenstrual treatment, which was balanced when delayed by estrogen withdrawal, triggering post-dosing migraine immediately after the gel was stopped (MacGregor et al 2006a). Furthermore, rising levels of estrogen appear to offer some protection against migraine (MacGregor et al 2006b).…”
Section: Female Sex Hormone (Estrogen and Progesterone) Receptorsmentioning
confidence: 99%
“…Furthermore, rising levels of estrogen appear to offer some protection against migraine (MacGregor et al 2006b). Thus, estrogen patches have been utilized to prevent the rapid decline of estrogen levels during the menstrual cycle (MacGregor 2006;MacGregor et al 2006a;MacGregor et al 2006b;MacGregor and Hackshaw 2002;Magos et al 1983), which is thought to be the main trigger of migraine in these patients (MacGregor 2006). These studies have reported mixed results ranging from no improvement to 80% improvement and are also based on a relatively limited number of patients (n=11-38).…”
Section: Female Sex Hormone (Estrogen and Progesterone) Receptorsmentioning
confidence: 99%
“…Maintaining luteal phase oestrogen levels can prevent menstrual attacks [MacGregor et al 2006;Somerville, 1975aSomerville, , 1975bSomerville, , 1972. Doses equivalent to 1.5 mg estradiol gel allow a mean estradiol plasma level of 80 pg/ml to be reached.…”
Section: Estradiolmentioning
confidence: 99%
“…There is evidence that some women responding to oestrogen supplements experience delayed attacks when the supplements are discontinued [MacGregor et al 2006] Oestrogen 'withdrawal' migraine may occur if treatment is not continued until the rise in endogenous oestrogen. Although there are no trial data, clinical practice suggests that for these women the duration of supplement use can be extended until day 7 of the cycle, tapering the dose over the last 2 days.…”
Section: Estradiolmentioning
confidence: 99%